Thermoreversible gelation of poly(vinylidene fluoride-co-hexafluoro propylene) in phthalates - Yadav P.J.P.; Aswal V.K.; Sastry P.U.; Patra A.K.; Maiti P. (My University, 2025)
The thermoreversible gelation of poly(vinylidene fluoride-co-hexafluoro propylene) copolymer have been studied in a series of phthalates, Ph-(COO C nH2n+1)2 with n = 1-8. The gelation rate increases with increasing aliphatic chain length up to n = 6, and the gelation phenomena does not occur for higher n > 6. The fibrillar morphology is evident for dried gels whose dimension (both lateral and thickness) becomes shorter and thinner with increasing n. The structures of the gels formed in various phthalates have been investigated by small-angle neutron scattering and small-angle X-ray scattering techniques, suggesting sheet-like structure, where the interplanner distance increases with increasing aliphatic chain length. The scattering intensity I(q) decreases with q according to the Ornstein-Zernike model, where q = (4π/γ) sin θ (2θ and γ are scattering angle and wavelength of neutron) and the correlation length, ξ, assigned to the average distance between the neighboring crystallites, also increases with increasing aliphatic chain length of diesters. The detailed thermal analyses and phase diagrams of the copolymer gels have been studied in a wide range of phthalates. Further, polymer- solvent complexes leading to the formation of two distinct compounds have been reported. A systematic change of compound composition has also been observed in the whole range of phthalates studied here. On the basis of electronic structure calculation, a model has been proposed to elucidate the conformation of copolymer chain in presence of various phthalates and their complexes, which offer the cause of higher gelation rate for longer aliphatic chain length up to n = 6, no gelation phenomena occurs for n > 6, and formation of two copolymer-solvent compounds. The mechanical properties (storage modulus and viscosity) decrease with increasing aliphatic chain length of phthalates and realignment of fibrils occurs at particular frequency depending on the strength of fibrillar gels. © 2009 American Chemical Society.